A world dictionary of livestock breeds types and varieties - Mason, I.L. (1969)
This dictionary lists names that have sheep, horses, pigs, goats, buffaloes and asses on the basis of common origin, similarity of appearance or geographical proximity. It indicates which are synonymous, and recommends the form for English use. The information, given in an easily followed abbreviated form, includes place of origin or present distribution and economic use of the various breeds, types and varieties, their inter-relationships, a description of the “breed characters† leaste affected by environment, such as colour and horns, and the origin of the name. A useful innovationn in this edition is the inclusion of referneces to the formation of breed Societies and Hersbooks.